SSZ-13 molecular sieve membrane, preparation method and application in SF6 separation

High-quality SSZ-13 zeolite film was synthesized by wet ball milling, and four-channel hollow fibers were used as the substrate, which solved the problem of low recovery and purity in SF6 recovery, and achieved efficient N2/SF6 separation under wet conditions, which was suitable for industrial SF6 recovery.

CN119656884APending Publication Date: 2025-03-21NANJING TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411914900.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has problems with low recovery and purity in SF6 recovery, especially when water vapor is contained in the feed, the performance of the zeolite film is significantly deteriorated, and it is difficult to obtain pure SF6 in the inorganic microporous film.

Method used

High-quality SSZ-13 zeolite membrane was synthesized by wet ball milling, and four-channel hollow fibers were used as substrate. The influence of feed pressure, temperature, components and humidity on the separation performance of N2/SF6 mixture was studied, and the membrane performance was initially evaluated using CO2/CH4 separation.

Benefits of technology

The SSZ-13 zeolite membrane is efficiently separated under hydrothermal stability conditions, which improves the recovery rate and purity of SF6, and the membrane performance remains stable under humid conditions, which is suitable for industrial SF6 recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to an SSZ-13 molecular sieve membrane, a preparation method and an application of the SSZ-13 molecular sieve membrane in SF6 separation, and a high-quality SSZ-13 zeolite membrane is synthesized on a hollow fiber substrate and is used for N2 / SF6 separation. The ball-milled seed crystal more reliably synthesizes a thinner film. The thickness of the film layer induced and synthesized by the original seed crystal is 14 microns, and the thickness of the film layer induced and synthesized by the ball-milling seed crystal is 5.2 microns. The average N2 / SF6 selectivity is 325, and the N2 transmittance is 5.4 * 10 <-8 > mol.m <-2 >. S <-1 >. Pa <-1 > (-160 GPU).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an SSZ-13 molecular sieve membrane, a preparation method and application in SF6 separation, belonging to the technical field of molecular sieve membranes. Background Art

[0002] Based on the size exclusion effect, gas separation membranes have a certain potential for separating N2 (kinetic diameter 0.38 nm) and SF6 (kinetic diameter 0.51 nm). Polymer membranes were used to separate N2 / SF6. The N2 / SF6 selectivity of polysulfone (PSF) and polyimide membranes was 20~40, and the N2 permeability was 1~5 GPU (1 GPU = 3.3928 × 10 -10 mol·m -2 ·s-1·Pa -1 ). The N2 permeability of the matrix asymmetric membrane can be increased to 15.9 GPU by increasing the temperature (473 K). Recently, they designed a mobile separation system based on polyimide membrane with an effective separation capacity of 50 Nm3 / h. However, the enrichment factor (6.0) and recovery rate (40%) of 0.16% SF6 in semiconductor industrial flue gas using PSF membrane were low. In order to further improve the recovery rate and purity, multi-stage membrane treatment is required. At the same time, it is difficult to obtain pure SF6 due to the plasticization effect. Therefore, inorganic microporous membranes will be a better choice.

[0003] Zeolite membranes have attracted extensive attention in the separation industry for their high permeation flux and selectivity. SF6 molecules are often used as a probe to determine the quality of zeolite membranes. For example, Drobek et al. used the ideal N2 / SF6 selectivity to predict the ethanol / water selectivity of MFI zeolite membranes. Wang et al. quantified the permeability of He through the pores of DD3R and STT zeolites by assuming that SF6 only permeates through non-zeolite pores. However, the application of zeolite membranes in SF6 recovery has been rarely studied. Recently, Lee et al. proposed a separation system for enriching industrial SF6 using MFI or SAPO-34 zeolite membranes. In dry feed streams, the purity and recovery of SF6 were maintained above 99.7% and 90%, respectively. However, once water vapor appears in the feed, the performance deteriorates significantly. Poshusta et al. reported that the gas permeability of SAPO-34 zeolite membranes decreased by 99.2% once water vapor was adsorbed. The hydrothermal stability of SAPO-34 zeolite membranes is another obstacle to practical applications because the framework collapses during the hydrolysis reaction. Therefore, it is urgent to improve the water vapor resistance of zeolite membranes.

[0004] High-silica CHA zeolite membranes (SSZ-13) have been shown to be hydrothermally stable and efficient for gas separations of CO2 / N2, CO2 / CH4[20,21] and Kr / Xe. Yu et al. observed very low permeance of SF6 (~1 GPU) through defect-free CHA zeolite membranes. Recently, it was also demonstrated that SSZ-13 molecular sieves exhibit perfect size exclusion for SF6 molecules by gas adsorption. Therefore, high-quality SSZ-13 zeolite membranes have excellent separation performance for N2 / SF6 mixtures. Summary of the invention

[0005] The present invention synthesized high-quality SSZ-13 zeolite membranes using wet ball-milled zeolite as seeds. The formation mechanism of zeolite membranes was studied using pristine SSZ-13 zeolite as seeds. Four-channel hollow fibers were used as substrates due to their excellent mechanical strength and commercially favorable packing density. The performance of the membranes was preliminarily evaluated by CO2 / CH4 separation before separating N2 / SF6 mixtures. The effects of feed pressure, temperature, composition and humidity on the separation performance of N2 / SF6 mixtures were studied. The surface barrier created by bulky SF6 molecules to N2 permeation was well described.

[0006] A method for preparing a SSZ-13 molecular sieve membrane comprises the following steps: Step 1, preparing a synthesis solution, performing hydrothermal synthesis, separating and washing the product, calcining to remove the template, and using the product as seed crystal A; Step 2, ball milling the seed crystal A to reduce the average particle size to 300-400 nm and the relative crystallinity to 20-40%, thereby obtaining the seed crystal B; Step 3, preparing the seed crystal B into a water suspension with a concentration of 0.1-1 wt%, and applying it on the surface of the porous ceramic support; Step 4, placing the porous ceramic support in a synthesis liquid for hydrothermal synthesis to obtain a SSZ-13 molecular sieve membrane.

[0007] In the step 1, the template is TMAdaOH, the hydrothermal synthesis is at 400-450K for 80-120h, the calcination process is at 850-900K for 5-15h, and the heating and cooling rates of the calcination are 5-15 K / min.

[0008] In the steps 1 and 4, the composition of the synthetic liquid used is: 105 SiO2: 0.525 Al2O3: 20TMAdaOH: 11.81 Na2O: 4400 H2O.

[0009] In the step 2, the ball milling process is carried out at a rotation speed of 300-500 rpm and a ball milling time of 2-6 hours.

[0010] The above-mentioned SSZ-13 molecular sieve membrane is used for separating N2 / SF6 in mixed gas.

[0011] In the above application, the permeability of N2 is improved by increasing the temperature of the mixture, and the temperature is 400-450K.

[0012] The mixed gas also contains water vapor, which refers to saturated water vapor at 0.5-0.7 MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 : Characterization of seeds and seed substrates. (a) Particle size distribution, (b) PXRD pattern, (cd) SEM images of substrates seeded with seeds A and B.

[0014] Figure 2 : Surface and cross-sectional SEM images of the membranes. (A-B) In situ synthesis, (cd) Seed A, (ef) Seed B.

[0015] Figure 3 : SEM images of membranes induced by Seed A (A-f) and Seed B (gl). (ab, gh) were synthesized for 1 day, (cd, ij) for 2 days, and (ef, kl) for 3 days.

[0016] Figure 4 : Schematic diagram of seed crystals A and B forming zeolite membrane.

[0017] Figure 5 : Single gas permeability of SSZ-13 zeolite membrane at 298 K (a) Single gas permeability, (b) Ideal selectivity of N2 to other gas components, (c) SF6 permeability fitting P overall = k ∙∆ p + P Knudsen , (d) N2 permeability through zeolite () and non-zeolite pores.

[0018] Figure 6 :(a) Pressure / concentration dependence of N2 / SF6 separation performance and comparison with literature; (b) Effect of N2 content on N2 / SF6 separation performance at a feed pressure of 1.1 MPa.

[0019] Figure 7 :Effect of temperature on N2 / SF6 separation performance at a feed pressure of 0.5 MPa, open symbols: single gas permeation, closed symbols: equimolar mixture separation.

[0020] Figure 8: Stability of SSZ-13 zeolite membrane for separation of N2 / SF6 (1:9) mixture. Orange and blue regions: dry gas and wet gas feed, 303 K, green region: temperature-increasing activation, 423 K.

[0021] Synthesis of High-Silica CHA Zeolite Seeds Seed A: synthesized according to the prior art (H. Liu, X. Gao, S. Wang, Z. Hong, X. Wang, X. Gu, SSZ-13 zeolite membranes on four-channel α-Al2O3 hollow fibers for CO2separation, Sep. Purif. Technol. 267 (2021) 118611.); the preparation process is: Raw materials: sodium hydroxide, aluminum hydroxide, N,N,N-trimethyl-1-adamant ammonium hydroxide (TMAdaOH) solution, colloidal silica and deionized water. NaOH and Al(OH)3 were added to deionized water at room temperature and stirred for 2 h, then a certain amount of TMAdaOH was added. Finally, colloidal silica was added dropwise to the solution. The mixture was stirred for another 12 h at room temperature. Hydrothermal crystallization was carried out at 433 K for 96 h in a Teflon-lined autoclave. After hydrothermal synthesis, SSZ-13 crystals were recovered by centrifugation and washed with deionized water. The powder was dried at 333 K overnight. It was then calcined in air at 873 K for 10 h to remove the organic structure directing agent (OSDA). The heating and cooling rates were 10 K / min. During the specific synthesis process, the ratio of the synthesis liquid was adjusted, and the following synthesis liquid composition was adopted: 105 SiO2: 0.525 Al2O3: 20TMAdaOH: 11.81 Na2O: 4400 H2O.

[0022] Seed crystal B: obtained by ball milling seed crystal A using a planetary ball mill.

[0023] The synthesis conditions are shown in Table 1. The two seed crystals were dispersed in deionized water with a concentration of 0.5 wt.% to obtain a suspension for seeding.

[0024] Table 1 Seed synthesis and characterization

[0025] a : Relative crystallinity with a seed; b : Average particle size measured by DLS technology; c : Synthesis at 433 K for 96 h; d: Ball mill seeds A at 400 rpm for 4 h.

[0026] High-silicon CHA zeolite membrane prepared by secondary growth method High-silica CHA zeolite membranes were prepared by secondary growth method. Four-channel α-Al2O3 ceramic membranes with pore size of 3.6 mm, inner diameter of 0.9 mm, porosity of ~50%, and average pore size of 300 nm were used as supports, named as "four-channel hollow fibers", and were seeded by dip-coating technique before synthesis. The molar composition of the synthesis solution was: 105 SiO2: 0.525 Al2O3: 20 TMAdaOH: 11.81 Na2O: 4400 H2O. After crystallization at 433 K, the membranes were washed with deionized water and dried at 333 K overnight. The template was calcined in air at 753 K for 24 h, with heating and cooling rates of 0.5 K min-1. Results and Discussion Seed A is pseudo-conical in shape, with an average particle size of 660 nm ( Figure 1 a), the average particle size of B seeds is 360nm, because ball milling can effectively break up the crystals. However, large crystals still exist and even dominate in the SEM images. Large crystals can be removed by post-ball milling / milling treatment. Double-layer seeds are urgently needed to fabricate defect-free MFI zeolite membranes, where small seeds can effectively fill the gaps between large seeds. Along this line, the fragments within the ball-milled seeds will facilitate the seeding process of SSZ-13 zeolite. The PXRD spectrum of the ball-milled seeds is the same as that of standard CHA zeolite ( Figure 1 b). This result confirms the successful crushing of the initial zeolite without the formation of impurity phases, and the relative crystallinity is much lower than the initial crystallinity (Table 1).

[0027] A water suspension containing 0.5 wt.% of seed crystals was used to investigate its effect on immersion seeding. SEM images show that both seed crystals form a continuous layer ( Figure 1 cd). While the seed B layer is more uniform than the seed A layer, we speculate that the seed A is too large (660 nm) to effectively fill and level the substrate because the pore size is only 300 nm. The gaps between the large crystals are filled by the fragments of ball-milled seed B, which is more effective than the double-layer seeding method because one dip coating is sufficient.

[0028] After hydrothermal treatment at 433 K for 96 h, a well-grown continuous film was obtained. The surface grain size of the in-situ synthesized film was 14.3±2.2 μm, and the film thickness was about 20 μm ( Figure 2 Seed A induces the surface grain size of the film to decrease to 7.0±0.1 μm ( Figure 2c). The surface grain size of the film induced by seed B is 4.5±1.9 μm ( Figure 2 e). The film thickness decreases more significantly. The thickness of seed A decreases to ~14 μm ( Figure 2 d), the film thickness of seed B is only 5.2 μm ( Figure 2 f). Since seed B is smaller than seed A and the mass concentration of both suspensions is the same, the number concentration should be 6 times that of seed A. In this case, the number of crystals fixed on the substrate will be larger, and more nuclei will grow simultaneously from the ball-milled seed layer. The quality of the membrane was evaluated by separation of equimolar CO2 / CH4 and N2 / SF6 mixtures. At least four membranes were synthesized from each seed crystal at one time, and the gas separation performance is shown in Table 2. The average CO2 permeability of the four in situ synthesized membranes (M1~M4) was (2.1±0.3)× 10-6 mol·m -2 ·s -1 ·Pa -1 , which is higher than that of hollow fibers (5.1 × 10 -5 mol·m -2 ·s -1 ·Pa -1 ) is one order of magnitude lower. Together with the low selectivity of 1.6, it proves that the membrane is defective and cannot separate CO2 from CH4. The separation effect of N2 / SF6 mixture is also poor. The best membranes induced by seed A (M5~M8) have CO2 / CH4 separation factors comparable to those in the literature. However, the separation factors of M9~M14 are lower (17~88). The reason for the poor reproducibility may be the uneven seed layer. Since the zeolite shrinks and the alumina expands during the high-temperature calcination process, intercrystalline defects are formed. The separation factor of N2 / SF6 (5.6~25) is lower than that of CO2 / CH4. In particular, the SF6 permeability of membranes M9~M14 is as high as 10~40 GPU, indicating that the membrane is defective and SF6 only penetrates through non-zeolite pores. The CO2 / CH4 separation factors of the six membranes induced by seed B are all greater than 100, and the average N2 / SF6 separation factor is 325. The experimental results show that ball-milled seeds are a reliable raw material for preparing highly selective SSZ-13 zeolite membranes (M15-M20).

[0029] Table 2 Binary mixture separation performance of molecular sieve membranes

[0030] a : Impregnated with 0.5 wt.% seed suspension and hydrothermally treated at 433 K for 96 h; b : × 10 -7 mol·m -2 ·s -1 ·Pa-1 ; c : × 10 -8 mol·m -2 ·s -1 ·Pa -1 M1~M4 and M5~M20 were tested at feed pressures of 0.1 MPa and 0.2 MPa, respectively; with 50 mL / min of Ar and He as sweep gases, the separation of CO2 / CH4 and N2 / SF6 was carried out at 298 K.

[0031] Film formation mechanism To gain a deeper understanding of the film formation process, we recorded the film morphology and synthesis time. After 1 day of synthesis, seed A obtained a continuous film with a thickness of ~8 μm ( Figure 3 The film thickness induced by seed B is only 4 μm ( Figure 3 gh). The separation factors of CO2 / CH4 and N2 / SF6 were 33~79 and 10~18, respectively. More interestingly, as the synthesis time was extended to 3 days, the thickness remained basically at 4~5 μm. Seed A induced the membrane thickness to gradually increase to ~10 μm and finally to ~12 μm ( Figure 3 cf). At the same time, excessive crystals were observed, with a grain size of about 8.8 μm, which increased the roughness of the membrane surface. The membrane induced by seed B was relatively smooth. To visualize the formation of zeolite membranes, the effect of seeding on the formation of high-silicon CHA zeolite membranes is shown in Figure 2. Figure 4 As shown. Since the evolution of silica oligomers is the controlling step, we believe that the secondary growth of the seed crystals begins before the zeolite nucleates from the precursor. In general, ball-milled fragments are more active due to their small particles and large surface area. This will lead to preferential and rapid growth over the original product. At the same time, these small fragments will serve as nutrients for the zeolite through Ostwald ripening. Both results fill and level the low-lying areas of the seed layer, resulting in a smooth film layer. Further crystal growth is limited by steric hindrance, which leads to a relatively consistent film thickness. However, the zeolite film induced by Seed A is relatively rough, and the formed zeolite crystals are easy to attach. This well explains why there are excess crystals on the top surface of the membrane induced by Seed A. Separation performance evaluation The permeability of single gases was further tested using light gas molecules of different kinetic diameters. The permeability decreased in the order CO2 > H2 > He > N2 > CH4 > SF6 ( Figure 5 a). At 0.1 MPa, the permeability of CO2 reaches 1.4 × 10 -6 mol·m -2 ·s -1 ·Pa -1, even with a larger kinetic diameter, the permeability of CO2 is 5 times higher than that of H2. The preferential adsorption and rapid diffusion of CO2 are reasonable explanations. The ideal selectivity of CO2 / CH4 is 530, which far exceeds the membrane performance required for natural gas upgrading ( Figure 5 b). The ideal CO2 / N2 selectivity is 25, indicating that CO2 capture from flue gas has good application prospects. N2 permeability is 5.4 × 10-8 m -2 ·s -1 ·Pa -1 (160 GPU), the ideal selectivity of N2 / CH4 is 20, and the ideal selectivity of N2 / SF6 is 570, which is far higher than Knudsen selectivity. The results also confirm the application prospects of SSZ-13 zeolite membrane in denitrification of natural gas and SF6 exhaust gas.

[0032] SF6 permeates through non-zeolite pores only by Knudsen diffusion and viscous flow. Therefore, the SF6 permeability can be fitted by the popoall = k∙∆p + PKnudsen model ( Figure 5 c), where the coefficient k is attributed to viscous flow. The permeability of SF6 via Knudsen diffusion is 1.166 × 10 -10 m -2 ·s -1 ·Pa -1 (0.34 GPU), which is independent of the feed pressure. The permeability of SF6 in viscous flow increases linearly with the pressure difference. When the pressure increases to 1.6 MPa, the permeability of SF6 increases by 2.6 times, but the ideal selectivity of N2 / SF6 is still as high as 182. Although N2 molecules also permeate through non-zeolite pores, CHA zeolite pores contribute more than 99.1% of the N2 permeability ( Figure 5 All these results confirm the high quality of our SSZ-13 zeolite membrane. There are few studies on the separation performance of zeolite membranes for N2 / SF6 mixtures. The present invention uses an equimolar N2 / SF6 mixture and evaluates the performance of the membrane at a pressure of up to 1.6 MPa and a temperature of 298 K ( Figure 6a). As the overall SF6 permeability increases with increasing pressure, the N2 / SF6 separation factor decreases from 456 at 0.1 MPa to 133 at 1.6 MPa. But all of these properties are far beyond the upper limit of polymer membranes. Although the performance is slightly lower than that of SAPO-34 molecular sieve membranes. However, SAPO-34 zeolite membranes are sensitive to steam moisture and suffer from channel clogging or framework collapse. MFI zeolite membranes are resistant to water vapor, but due to their larger pores, the N2 / SF6 separation factor is limited to 30~50. The poor separation factor results in poor SF6 recovery, which is only 90.8% in a mixture containing 80% SF6. Therefore, the superior N2 / SF6 separation factor of our SSZ-13 zeolite membrane will be more conducive to the full recovery of SF6 and reduced emissions to the atmosphere. In order to evaluate the feasibility of SSZ-13 zeolite membrane in practical application, we also tested the N2 / SF6 separation performance under different feed compositions at 1.1 MPa and 298 K ( Figure 6 b). When the N2 concentration is 3%, the N2 transmittance is 3.8 × 10-8 m -2 ·s -1 ·Pa -1 (~110 GPU), with a N2 / SF6 separation factor of 203. In this case, the SF6 concentration in the permeate was 0.3%. The permeance of N2 fluctuated slightly, but the permeance of SF6 increased with increasing N2 concentration. This result may be related to the competitive adsorption of nitrogen and SF6 on the membrane surface. For a typical insulating gas with a N2 content of 70%, the SF6 concentration in the permeate side of the one-stage membrane process is as low as 800 ppm and can be discharged to the atmosphere without further treatment. However, to achieve this goal, a three-stage PRISM membrane operation at 319 K is required. This will consume more additional compression and heating energy, increasing the overall cost and energy demand.

[0033] To study competitive adsorption, we further separated the N2 / SF6 mixture at temperatures up to 423 K ( Figure 7 ). At 303 K, the N2 transmittance is 4.6 × 10 -8 mol·m -2 ·s -1 ·Pa -1, decreases monotonically with increasing temperature. This is in contrast to commercial polymer membranes (e.g., polysulfone, matrix, polyimide), where the N2 permeance increases with increasing temperature. The permeation of N2 through zeolite membranes is described by surface diffusion. In this case, gas absorption usually dominates the N2 / SF6 separation, especially at room temperature or low temperatures. This is why SF6 molecules are strongly adsorbed in the MFI zeolite channels, resulting in preferential permeation of SF6 over N2. Due to the strong particle size exclusion effect, SSZ-13 molecular sieve membranes exhibit N2 selective permeation for SF6. However, the N2 permeance and selectivity in the mixture are always lower than those of the single component.

[0034] To visualize the slowing effect, we calculated the normalized nitrogen permeability by dividing the nitrogen permeability in the mixture by that in the pure component (Table 3). The normalized N2 permeability decreases from 0.90 at 303 K to 0.85 at 333 K and stabilizes at 0.81 above 363 K. This is different from the case of propane, where the normalized nitrogen permeability decreases to 0.56. Propane molecules can penetrate the 8MR window that accommodates the CHA cage. The blocking effect is more pronounced for water molecules. In contrast, the absorption of SF6 occurs only on the outer surface of the CHA zeolite, which acts as a surface barrier to the permeation of N2.

[0035] Table 3 SSZ-13 membrane N2 permeability (P N )

[0036] a: The normalized N2 permeability is defined as the ratio of the N2 permeability after impurity induction to the initial permeability; b: The normalized N2 permeability is defined as the ratio of the N2 permeability in 50 / 50 N2 / SF6 to the N2 permeability in pure nitrogen.

[0037] Since water vapor is always present in the atmosphere, dry insulating gas becomes humid after mixing with air. Although SSZ-13 zeolite membranes are hydrothermally stable under humid conditions, the impact on N2 / SF6 separation performance has not been addressed. Here, we evaluated the performance of the membranes in the presence of 0.6 MPa saturated water vapor and room temperature ( Figure 8 ). In a dry binary mixture, the N2 permeability is 3.8 × 10-8 mol·m -2 ·s -1 ·Pa -1, the N2 / SF6 separation factor was 250. When the feed was saturated with water vapor, the permeabilities of both N2 and SF6 decreased. However, the N2 permeability was greatly affected, with only 1 / 3 remaining, resulting in a reduction in the N2 / SF6 separation factor to 110. This is due to the moisture absorption in the CHA cages and the non-zeolite boundaries delaying the material transport. However, due to the hydrophobicity of the high-silica CHA zeolite, the N2 permeability gradually recovered after the humidified gas supply was terminated, reaching 88% of the initial performance within 2 h. However, it was difficult to recover the initial SF6 permeability even after heating at 423 K for 7–14 h. Unlike the CHA cages, the non-zeolite pores are modified by hydroxyl groups, resulting in strong adsorption of water molecules. In this case, the permeation of SF6 via Knudsen diffusion and viscous flow was more hindered due to the partial blockage of the non-zeolite pores. After two humidified feed cycles for a total of 65 h, the performance of the membrane remained unchanged, confirming the reliable stability of the SSZ-13 zeolite membrane for the separation of wet-saturated N2 / SF6 mixtures.

Claims

1. A method for preparing SSZ-13 molecular sieve membrane, characterized in that: The steps include: Step 1, preparing a synthesis solution, performing hydrothermal synthesis, separating and washing the product, calcining to remove the template, and using the product as seed crystal A; Step 2, ball milling the seed crystal A to obtain the seed crystal B; Step 3, preparing the seed crystal B into a water suspension with a concentration of 0.1-1 wt%, and applying it on the surface of the porous ceramic support; Step 4, placing the porous ceramic support in a synthesis liquid for hydrothermal synthesis to obtain the SSZ-13 molecular sieve membrane.

2. The method for preparing the SSZ-13 molecular sieve membrane according to claim 1, characterized in that: The ball milling process needs to reduce the average particle size to 300-400nm and the relative crystallinity to 20-40%.

3. The method for preparing the SSZ-13 molecular sieve membrane according to claim 1, characterized in that: In step 3, the concentration of the aqueous suspension is 0.1-1 wt %.

4. The method for preparing the SSZ-13 molecular sieve membrane according to claim 1, characterized in that: In the step 1, the template is TMAdaOH, and the hydrothermal synthesis is performed at 400-450K for 80-120h.

5. The method for preparing the SSZ-13 molecular sieve membrane according to claim 1, characterized in that: The calcination process is 850-900 K for 5-15 h, and the heating and cooling rates of the calcination are 5-15 K / min.

6. The method for preparing the SSZ-13 molecular sieve membrane according to claim 1, characterized in that: In the steps 1 and 4, the molar ratio composition of the synthetic liquid used is: 105 SiO2: 0.5-0.6Al2O3: 20 TMAdaOH: 11-13Na2O: 4000-5000 H2O.

7. The method for preparing the SSZ-13 molecular sieve membrane according to claim 1, characterized in that: In the step 2, the ball milling process is carried out at a rotation speed of 300-500 rpm and a ball milling time of 2-6 hours.

8. Application of the SSZ-13 molecular sieve membrane obtained by the preparation method of claim 1 in separating N2 / SF6 in mixed gases.

Citation Information

Cited By

  • Preparation method of hollow fiber membrane separator and method for separating sulfur hexafluoride and nitrogen

    CN121016498A

  • A method of manufacturing a hollow fiber membrane separator and a method for separating sulfur hexafluoride and nitrogen

    CN121016498B